2013
DOI: 10.3892/etm.2013.1241
|View full text |Cite
|
Sign up to set email alerts
|

Artificial and bioartificial liver support systems for acute and acute-on-chronic hepatic failure: A meta-analysis and meta-regression

Abstract: Artificial and bioartificial liver support systems (LSSs) appear to be safe and effective in the treatment of acute and acute-on-chronic hepatic failure (AHF and AOCHF); however, individually published studies and previous meta-analyses have revealed inconclusive results. The aim of the present meta-analysis was to derive a more precise estimation of the benefits and disadvantages of artificial and bioartificial LSSs for patients with AHF and AOCHF. A literature search was conducted in the PubMed, Embase, Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 35 publications
(32 reference statements)
2
33
1
2
Order By: Relevance
“…Although both studies used similar methodologies, the previous meta-analysis included nonrandomized trials. 6 In contrast to our study, another recently published metaanalysis 29 found a mortality benefit of artificial liver support systems over standard medical therapy in patients with acute-on-chronic liver failure. The study did not focus on albumin dialysis and included studies that compared albumin dialysis, hemoperfusion, hemofiltration, and the BioLogic-DT sorbent suspension dialyzer to standard medical therapy.…”
Section: Discussioncontrasting
confidence: 66%
“…Although both studies used similar methodologies, the previous meta-analysis included nonrandomized trials. 6 In contrast to our study, another recently published metaanalysis 29 found a mortality benefit of artificial liver support systems over standard medical therapy in patients with acute-on-chronic liver failure. The study did not focus on albumin dialysis and included studies that compared albumin dialysis, hemoperfusion, hemofiltration, and the BioLogic-DT sorbent suspension dialyzer to standard medical therapy.…”
Section: Discussioncontrasting
confidence: 66%
“…Finally, the number of studies included in this meta-analysis was relatively small; however, in a previous systematic review (29) investigating the characteristics of meta-analyses and their included studies in the Cochrane Database, it was revealed that, irrespective of the medical field, relatively few studies are typically eligible for meta-analysis for all outcomes and interventions covered by the Cochrane reviews. Furthermore, the methodological quality of the studies included in a meta-analysis has a greater impact on the estimated effects than the numbers of included studies (30,31). QUADAS assessment revealed a high overall quality of the studies included in the present meta-analysis.…”
Section: Per-patientmentioning
confidence: 84%
“…Commonly used methods to counteract HE may be divided into several types according to treatment access: Administration via the oral, rectal or intravenous routes; artificial liver transplantation; and full liver transplantation (9)(10)(11)(12)(13). Oral drugs mainly act by reducing the production and absorption of ammonia.…”
Section: Introductionmentioning
confidence: 99%